Wave Height Characteristics Due to The Influence of Land and Sea Breezes on Fishermen’s Activities in The Coastal Area of Makassar City Using Doppler Weather Radar - Pertiwi, Dini Afiaty; Asbar, Asbar; Jamal, Muhammad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Makassar City, located on the southwest coast of Sulawesi Island, exhibits dominant land and sea breeze circulation, with sea breezes being stronger during the day and land breezes at night. The use of weather radar is effective in identifying these wind characteristics, which are crucial for fishing activities and renewable energy. This study investigates the characteristics of land and sea breezes and their relation to wave heights in the Spermonde Waters of Makassar during the east and west seasons, providing important information for maritime activities in Makassar City. The research area is located between 4°59’20”S 119°27’46”E and 5°11’26”S 119°22’54”E. This study uses weather observation data, including weather radar data, weather observations, and wave heights from January 2020 to December 2020, divided into three seasonal periods (rainy season, transition period, and dry season). The weather observation data were obtained from Hasanuddin Makassar Meteorological Station and Paotere Makassar Maritime Meteorological Station. Additionally, questionnaires were distributed to fishermen at three locations: PPI Paotere Makassar, PPI Untia Makassar, and Kuri Caddi-Maros Beach Fishermen Village, with 15 respondents at each location. The study shows that land breezes in Makassar are dominant from 18:05 to 19:00 LT with a duration of 9.1 to 11 hours, while sea breezes dominate from 08:00 to 09:00 LT with a duration of 5.1 to 7 hours. This phenomenon is most frequently detected during the dry season (JJA). Land and sea breezes can intrude up to 20.1 to 30 km from the coastline. There is a highly significant positive correlation between wind and wave height in January and August, indicating a strong influence of winds on waves in the Spermonde Waters of Makassar. About 80% of fishermen utilize these wind conditions for fishing activities. Overall, the land and sea breeze patterns significantly impact wave heights and the activities of fishermen in the coastal areas of Makassar.